Decoding the microbial universe with metagenomics: a brief insight - Chaudhari, Hiral G.; Prajapati, Shobha; Wardah, Zuhour Hussein; Raol, Gopal; Prajapati, Vimalkumar; Patel, Rajesh; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I.; Sayyed, R. Z. (Frontiers in Genetics, 2023)
A major part of any biological system on earth involves microorganisms, of which the majority are yet to be cultured. The conventional methods of culturing microbes have given fruitful outcomes yet have limitations. The curiosity for better understanding has led to the development of culture-independent molecular methods that help push aside the roadblocks of earlier methods. Metagenomics unifies the scientific community in search of a better understanding of the functioning of the ecosystem and its component organisms. This approach has opened a new paradigm in advanced research. It has brought to light the vast diversity and novelty among microbial communities and their genomes. This review focuses on the development of this field over time, the techniques and analysis of data generated through sequencing platforms, and its prominent interpretation and representation.